Distributed Sensor Network-Based Virtual FDR System - Kwang-Ho Seok; Junho Ko; Chul-Won Park; Chul-Hwan Kim; Yoon Sang Kim (International Journal of Distributed Sensor Networks, 2013)
We propose an application for power facility monitoring using distributed sensor networks. The proposed application is a virtual frequency disturbance recorder (FDR) system that estimates the frequency of a power grid using the data from a modeled grid and sends the information to the server for monitoring via wireless communication. To verify the validity of the proposed application, we conducted experiments using actual system data. The functionality of the proposed system was also verified by establishing a ZigBee-based wireless network for power monitoring and diagnosis of disturbances.